2019
DOI: 10.5812/iji.97033
|View full text |Cite
|
Sign up to set email alerts
|

Co-Infection of Malaria and Hepatitis B Virus in Port Harcourt, Rivers State, Nigeria

Abstract: Background: Malaria and hepatitis B virus (HBV) are two diseases of major medical importance in Nigeria. Methods: The study determined the preponderance of malaria, HBV and their co-infection among 600 outpatients of three major hospitals in Port Harcourt, Nigeria, using standard microscopic method and rapid serology assay diagnostic kit. Results: Total preponderance rate of malaria, HBV, and co-infection was observed to be 41.0%, 6.0%, and 4.33%, respectively. The female gender was more infected with malaria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 12 publications
1
16
2
Order By: Relevance
“…The 6.3% prevalence for hepatitis B observed in this study is lower than the 19.0% prevalence reported by Kolawole and Kana (15) among febrile patients attending general and specialty hospitals in Ilorin, Kwara State. Although lower prevalence rates have been reported for hepatitis B in some parts of Nigeria (15), the hepatitis B prevalence recorded in this study is consistent with the 6.5% and 6.0% rates earlier reported from the Northern and Southern parts of Nigeria, respectively (16)(17)(18). This consistency may be due to the similarity in the socio-demographic characteristics and laboratory methods used for the analyses.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The 6.3% prevalence for hepatitis B observed in this study is lower than the 19.0% prevalence reported by Kolawole and Kana (15) among febrile patients attending general and specialty hospitals in Ilorin, Kwara State. Although lower prevalence rates have been reported for hepatitis B in some parts of Nigeria (15), the hepatitis B prevalence recorded in this study is consistent with the 6.5% and 6.0% rates earlier reported from the Northern and Southern parts of Nigeria, respectively (16)(17)(18). This consistency may be due to the similarity in the socio-demographic characteristics and laboratory methods used for the analyses.…”
Section: Discussionsupporting
confidence: 90%
“…Of many types of HPV, about 30 types can infect the genital tract through sexual contact. Genital HPV 16,18,31, and 45 account for more than 90% of cervical carcinomas (2)(3)(4). Cervical cancer and premalignant lesions make major problems in women's health.…”
Section: Introductionmentioning
confidence: 99%
“…When assessing the individual studies, Plasmodium spp. and HBV co-infection was prevalent in most tropical and sub-Saharan African countries, particularly Nigeria [10,15,16,26,[28][29][30][31][33][34][35][36], Ghana [8,23,25], Central African Republic [24], and The Gambia [11]. The pooled prevalence estimate of Plasmodium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 9 studies [8][9][10][23][24][25][26][27][28] were included in the quantitative synthesis. Thirteen additional studies [11,[14][15][16][17][29][30][31][32][33][34][35][36] were identified and included after reviewing the references of the nine included studies and additional searches of other databases. The main characteristics of the 22 included studies [8-11, 14-17, 23-36] are presented in Table 1.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation